Current issues of pedagogy and psychology - Pronin A. Y., Konoplyansky D. A., Egorova G. V., Ryspaeva C. K., Ivanovskaia E. A., Orekhova S. E., Sivak O. A., Shevtsova A. V., Vinogradova I. A., Liakhova E. G., Khotuliova O. V., Medvedeva N. V., Novoselov K. A., Osipova A. A., Grigorev E. N., Khaibullin A. R., Fakhretdinova G. F., Zagrevskii V. I., Lavshuk D. A., Klochkov A. V., Sitdikova G. R., Malakhova L. A., Serova Z. N., Aleksandrov S. G., Satybaldieva R. A., Glotova G. A., Shipilova E. S., Koreneva A. V., Prisakaru E. I., Kazkanova C. T., Mukambetova G. B., Kazkanova C. T., Spiridonov E. A., Vasileva I. S., Shvaikina N. S., Pavlenko S. A., Akhmadeeva E. V., Pavlenko S. A., Zaluzhnaia M. V., Lavrentev M. V., Sulimin A. N., Khasin V. V., Churkina A. S. (Current issues of pedagogy and psychology, 2025)
the chapter considers the competence-based approach in the system of higher pedagogical education as an important factor in the formation of pedagogical tolerance in students. The structure of pedagogical tolerance as a component of professional competence of a future teacher is analyzed, the importance of interpersonal and value attitudes in the educational process is emphasized. Particular attention is paid to the integration of tolerance attitudes into academic disciplines, pedagogical practice and interaction in the educational environment. Substantiates the need for systematic work on the development of tolerance through competence-oriented teaching technologies. The directions of the university's work on the formation of students' ability for constructive dialogue and respectful interaction in pedagogical activity are presented.
Keywords: профессиональная компетентность; педагогическое образование; компетентностный подход; педагогическая подготовка; professional competence; межкультурное взаимодействие; педагогическая толерантность; будущий учитель; pedagogical education; future teacher; competence-based approach; intercultural interaction; pedagogical training; воспитание толерантности; pedagogical tolerance; tolerance education